Weekly Training Load Differences between Starting and Non-Starting Soccer Players - Varjan, Matej; Hank, Mikulas; Kalata, Maros; Chmura, Paweł; Mala, Lucia; Zahalka, Frantisek (Journal of human kinetics, 2024)
The aim of this study was to examine the differences in the weekly training load between starters and non-starters classified based on the match starting line-up, with respect to the playing position and a training day. Notably, 31 young adult soccer players (age: 18.79 ± 1.04 years) competing in the 3rd Czech division were monitored across the season. The weekly training load was measured using a GPS system as follows: total distance covered (TD), high-speed running distance (HSR), sprint running distance (SR), and acceleration and deceleration distance (ACDC). We found higher values in three out of four observed variables (HSR, SR, and ACDC, excluding TD) for starters compared to non-starters (p < 0.05), with small to moderate effect sizes (d = 0.40-0.49). Differences were observed especially in players who were fullbacks, offensive midfielders, and forwards. Moreover, the largest differences were found in training prior to a match day for HSR, SR, and ACDC (p < 0.05). Non-starters experienced lower weekly external loads in offensive player positions, predominantly in high-intensity variables, which are essential for their physical performance. It seems that non-starters may experience potential under-loading in the training process. Coaches and practitioners should be aware of this potential risk and find an appropriate method to compensate for load discrepancies, particularly in terms of high-intensity activities.
Keywords: physical performance; monitoring; player development; external load